(untitled) (Research, Society and Development, 2020)
Chlamydia trachomatis (CT) is a Gram negative bacterium that parasitizes eukaryotic cells, most frequently in the female cervix, causing several consequences to the health of women. It presents two forms, the first called elementary bodies (EC) being the infectious and resistant form that survives in the extracellular environment and the second, called reticular bodies (CR), the proliferative form of the bacterium. CT is a very virulent pathogen, with more than twenty serotypes that cause serious pathologies in humans. The present study sought to estimate the prevalence of Chlamydia trachomatis in the Brazilian population, highlighting the epidemiology, characteristics of the bacterium, the importance of its diagnosis and treatment A literature review was carried out based on studies of articles published between 2009 and 2018, in Portuguese, English and Spanish, with a total of 41 articles selected. In Brazil, the diagnosis and monitoring of infections by this microorganism is not yet a reality and there are few studies related to the theme, showing a high prevalence of the infection. Therefore, the lack of monitoring and diagnosis of this pathogen may lead to future complications, since the long-term result of infection and the promotion of infertility is seen in several studies. Female patients are the most affected by these pathogens, yet complications can be reported in males.